2003
DOI: 10.1038/sj.ijo.0802284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two breakfasts, different in carbohydrate composition, on hunger and satiety and mood in healthy men

Abstract: OBJECTIVE:To study the effect of simple vs complex carbohydrates (SCHO and CCHO respectively) containing breakfasts on blood parameters, hunger and satiety and mood. DESIGN: A 2-day, open, randomised, cross-over trial. SUBJECTS: A total of 26 male subjects (3476 y; BMI 23.472.2 kg m À2 ). MEASUREMENTS: Blood glucose, insulin, triacylglycerols (TG), free fatty acids (FFA) and cholecystokinin (CCK) were determined repeatedly for 4 h on both test days after a breakfast containing SCHO or CCHO. Feelings of hunger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…We found no differences between the different test meals. In a study by Pasman et al [9], it was shown that a breakfast consisting of mainly complex carbohydrates was less tiring than a breakfast with simple carbohydrates. The observed difference in their study could be due to the use of a different questionnaire assessing mood and a different composition of the test meals, which were more complex than in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no differences between the different test meals. In a study by Pasman et al [9], it was shown that a breakfast consisting of mainly complex carbohydrates was less tiring than a breakfast with simple carbohydrates. The observed difference in their study could be due to the use of a different questionnaire assessing mood and a different composition of the test meals, which were more complex than in our study.…”
Section: Methodsmentioning
confidence: 99%
“…After completion of the questionnaires, volunteers ate the test yoghurts over 15 min, which is a well-established time scale in these kinds of studies [9]. Immediately afterwards and then in 30-min intervals the 2 questionnaires were repeatedly filled out over a total period of 3 h with a total of 8 assessments conducted.…”
Section: Test Proceduresmentioning
confidence: 99%
“…4 Having $1 of the 3 assessed disorders (depression, distress, and anxiety). diet on depression and cognitive impairments in individuals with type 2 diabetes (26,27), others have reported a detrimental effect of high-GL or high-GI diets on subclinical depression, mood, and cognitive performance either in healthy individuals or in patients with diabetes (28)(29)(30)(31). Considerable differences in the design of studies, methods of assessment of psychological disorders, evaluation of dietary intakes, and duration of clinical trials might have contributed to these differences.…”
Section: Tablementioning
confidence: 99%
“…In addition, high-GI and high-GL diets may contain lower amounts of fiber, fruit, vegetables, and whole grains (23)(24)(25) and, consequently, provide lower amounts of some key nutrients for the nervous system compared with low-GI and low-GL diets, and, thus, may adversely affect mood disorders. However, findings in this context have been controversial in clinical trials (26)(27)(28)(29)(30)(31) and observational and longitudinal studies (32)(33)(34)(35)(36). Interpretation of these studies is potentially confounded by variations in study designs and durations, participant populations, and other attributes of diet, with study results not simply being distinguished by GI compared with GL.…”
Section: Introductionmentioning
confidence: 99%
“…The bean flake meal produced almost twice the CCK AUC0-360 response, which was statistically significant. Pasman et al compared the effect of isoenergetic meals containing complex or simple carbohydrates in 26 male volunteers (Pasman, Blokdijk, Bertina, Hopman & Hendriks, 2003). The complex carbohydrate meal contained 6.7 g of fiber, provided primarily by rye bread.…”
Section: Effect Of Fiber On Cholecystokinin Concentrationsmentioning
confidence: 99%